Safety and Efficacy of Supratarsal Triamcinolone for Treatment of Vernal Keratoconjunctivitis in Ireland. Issue 8 (August 2019) - McSwiney, Terence J.; Power, Barry; Murphy, Conor C.; Brosnahan, Donal; Power, William
Abstract : Purpose: To describe the clinical features, risk factors, and treatment outcomes after supratarsal injection of triamcinolone for vernal keratoconjunctivitis (VKC). Methods: A retrospective review of all patients treated with supratarsal triamcinolone for VKC between February 2002 and May 2017 at the Royal Victoria Eye and Ear Hospital and Our Lady's Children Hospital Crumlin, Dublin, Ireland, was performed. Results: Twenty-five patients, 46 eyes, and 145 injections were included for analysis. The mean age at first injection was 9.1 ± 5.7 years. Ninety-six percent of the patients were male. A seasonal variation was noted, with 59 injections (41%) of triamcinolone administered for acute and refractive cases of VKC in the summer compared with 35 (24%), 35 (24%), and 16 (11%) in the spring, autumn, and winter months, respectively. The most common presenting complaint was red eye, which was seen in all cases. Hay fever (64%) was the most common associated systemic disease. Each eye required, on average, 3.2 injections (range 1–9 injections), and the mean duration from the onset of symptoms to final treatment was 3.03 years (range 0–7.9 years). The mean presenting and final visual acuities were 0.33 and 0.11 logarithm of the minimum angle of resolution, respectively ( P < 0.0001). During our study period, no patient experienced intraocular pressure rise requiring treatment, development of lenticular opacity, or ptosis after supratarsal injection of triamcinolone. Conclusions: In this case series, supratarsal triamcinolone was used in cases of VKC in which topical medications had failed to control the disease process. All patients reported improvement after treatment. There were no cases of intraocular pressure rise, lenticular opacity, or ptosis development after treatment.